THE USE OF FLASHCARD GAME IN IMPROVING STUDENTS’ READING COMPREHENSION OF TENTH GRADE STUDENTS - Retno Rizki Septian Retno; Dias Andris Susanto; Ajeng Setyorini (STKIP Subang, 2023)
This research concentrated in the use of flashcard game in improving students’ reading comprehension. The objective of this research were: (1) to find out students’ reading comprehension scores before taught using the flashcard game as learning media, (2) to find out students’ reading comprehension scores after taught using the flashcard game as learning media, (3) to discover the significant different of using flashcard game in improving students’ reading comprehension. This research used quantitative pre-experiment research design. This research used one group pre-test and post-test design. The procedure of data collection were test and treatment. This research used SPSS to analysis the data to know whether there was a significant difference on students’ reading comprehension before and after taught using flashcard game as the teaching media. The result showed that the students reading comprehension score before taught using the Flashcard Game is 60,27 and the students reading comprehension score after taught using the Flashcard Game is 86,25. The result of the hypothesis testing showed that the value of the t-test was greater than the value of the t-table (10,834 > 1,689). It means H0 is rejected and H1 is accepted. The result of the research showed that the there was an improvement of the students’ reading comprehension by using the flashcard game as the teaching media for tenth grade students.